(untitled) (New Yorks, 1997)
Written by over 200 medical experts, this manual covers human diseases and disorders, from pregnancy and infancy through adult maturity, as well as providing details of prescription and over-the-counter medications, including use and interaction.
Keywords: Y học, phổ biến,Medicine, popular